TRANSITIVITY ANALYSIS OF GAVIN EUGENE LONG'S SUICIDE NOTE: A FORENSIC LINGUISTIC STUDY - Hayuwardhani, Aurelia Reza (Universitas Muhammadiyah Surakarta, 2019)
Gavin Eugene Long was a gunman who did a mass shooting in Baton Rouge in 2016. Before he was dead, a suicide note was left. The suicide note was a potential proof to investigate the deeds he wanted to convey before he was dead. Such phenomenal note deserves to be contested as the case for the present study. Therefore, this study aims atÂ understanding the note as seen through from forensic linguistic point of view. To understand the note, Forensic Linguistic (FL) study is required to do since suicide note is in the domain of it. Since FL relies upon linguistic analysis, Hallidayâ€™s Systemic Functional Linguistic (SFL) framework is applied. In the framework, ideational metafunction is chosen to be observed. The results of the observation show that the transitivity processes employed in the note reflect the deeds Long wanted to convey in relation to the mass shooting he did. Keywords: forensic linguistic, suicide note, systemic functional linguistic, transitivity.